2007
DOI: 10.1111/j.1399-3038.2006.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Action of a silk fabric treated with AEGISTM in children with atopic dermatitis: A 3‐month trial

Abstract: Irritation of the skin of patients with atopic dermatitis by contact with rough fibres of synthetic or woollen clothes is well known. Therefore, it has been recommended that patients should wear cotton clothes. However, cotton also consists of rough fibres able to irritate the skin, whereas silk is characterized by smooth fibres without irritating potential. The aim of our study was to evaluate the clinical effect of Dermasilk- a special silk fabric (sericin-free silk treated with AEGIS AEM5772/5 which has ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 11 publications
0
34
0
1
Order By: Relevance
“…The two studies on DermaSilk by Koller and colleagues 338 and Stinco and colleagues 339 reported that there were no adverse events during the study periods. The trial by Fontanini and colleagues 340 did not report information about adverse events.…”
Section: Harmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two studies on DermaSilk by Koller and colleagues 338 and Stinco and colleagues 339 reported that there were no adverse events during the study periods. The trial by Fontanini and colleagues 340 did not report information about adverse events.…”
Section: Harmsmentioning
confidence: 99%
“…[338][339][340] In 2007, Koller and colleagues 338 published a trial comparing DermaSilk arm tubes against ordinary silk arm tubes. Twenty-two children with mild to moderate eczema were included in the trial.…”
Section: Silkmentioning
confidence: 99%
“…10,11 To identify RCTs published prior to the CLOTHES trial, we searched the Global Resource of Eczema Trials database. 12 At the time of starting the CLOTHES trial, 14 small RCTs assessing the effects of therapeutic clothing had been published: three RCTs investigated silk clothing [DermaSilk TM (AlPreTec Srl, San Donà di Piave, Italy)]; [13][14][15] two investigated silver-coated textiles; 16,17 three investigated cellulose seaweed fibres with silver; [18][19][20] one investigated cellulose; 21 one investigated an anion textile; 22 two investigated types of ethylene vinyl alcohol fibre; 23,24 one investigated borage oil-coated garments; 25 and one investigated cotton and synthetic fibres. 26 Since the start of the trial, an additional study on chitosan-coated textiles has been published.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…Senti et al[ 13] observed no significant difference between DermaSilk-treated and corticosteroid-treated skin and suggested that this special textile would probably have an efficacy similar to a modern class III topical corticosteroid applied daily for a week. Koller et al[ 14] compared three different tube fabrics: DermaSilk, sericin-free silk fabric without AEGIS AEM 5772/5 and cotton. A significant reduction of the mean local SCORAD index of the DermaSilk-covered arm was observed in comparison with cotton- and AEGIS-free-silk-covered arms.…”
Section: Discussionmentioning
confidence: 99%